2004
DOI: 10.1016/j.jvs.2004.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reduction of medial and intimal thickening in porcine saphenous vein grafts with a polyglactin biodegradable external sheath

Abstract: Arteriovenous bypass graft failure has a huge economic effect on health care resources, and a devastating effect o the patient. The attenuation of vein wall thickening, with subsequent luminal narrowing and occlusion, is a major goal in improving the longevity of the venous graft, to reduce secondary percutaneous and surgical interventions. The biodegradable external stent demonstrated in this study has possible clinical applications in bypass procedures with autogenous venous tissue, and represents a novel ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 40 publications
4
83
0
Order By: Relevance
“…In addition, external support may have a role in redirecting vascular smooth muscle cell migration through a reversed chemotactic gradient. Neutrophils and monocytes that aggregate around the external support (in the context of foreign body reactions as also shown in our study) release chemo-attractive proteins that attract smooth muscle cells and fibroblast to the external support [23].…”
Section: Resultssupporting
confidence: 71%
“…In addition, external support may have a role in redirecting vascular smooth muscle cell migration through a reversed chemotactic gradient. Neutrophils and monocytes that aggregate around the external support (in the context of foreign body reactions as also shown in our study) release chemo-attractive proteins that attract smooth muscle cells and fibroblast to the external support [23].…”
Section: Resultssupporting
confidence: 71%
“…Preventing acute distension of AVGs by adding an external structural support (or sheath) has seemingly improved the patency of vein grafts [26,31,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] i) The biodegradation rate of the wrap must be tunable…”
Section: List Of Tablesmentioning
confidence: 99%
“…They showed that the sheath prevented dilatation, that it was well accepted by the host tissue, and that there was no difference in the tensile strength between supported and nonsupported vessels [50]. Karayannacos effects included enhanced neo-vasa-vasorum development over unwrapped controls [51].…”
Section: Previous Attempts To Wrap Arterial Vein Graftsmentioning
confidence: 99%
See 2 more Smart Citations